Analisis Faktor Karakteristik dan Manfaat Praktik Kesadaran Penuh (Mindfulness) dalam Proyek Konstruksi - Seng Hansen (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2025)
As one of the labor intensive sectors, human resources play an important role in the construction industry. Fulfilling various aspects of welfare, including the mental health of construction workers, is something that construction organizations must pay attention to. Mindfulness practices can be used as an effort to maintain and improve workers' mental health. However, there is a research gap regarding mindfulness practices in the Indonesian construction sector. This research aims to identify various characteristics and benefits of mindfulness practices in the context of the Indonesian construction industry. This research applies a mixed method approach with two data collection sequences, namely integrative literature review and questionnaire survey. The results of the literature review were used as input in developing the questionnaire. The collected data were analyzed using exploratory factor analysis to identify the latent factors related to the characteristics and benefits of mindfulness practice. This research succeeded in finding four latent characteristic factors of mindfulness, namely positive attitude, present-moment attention, openness, and non-striving. This research also identified five latent factors for the benefits of mindfulness, namely direct benefits, cognitive benefits, affective benefits, benefits at work, and further benefits. This research is important considering the close relationship between mindfulness practices and the mental health and well-being of construction workers.